Isolation of Chitosan From Dogol Shrimp Skin (Parapenaeopsis sculptilis) - Anggreini, Dea; Yuandani, Yuandani; Sinaga, Siti Morin (International Journal of Science, Technology & Management, 2023)
In Indonesia, shrimp underwent a "cold storage" process where the heads, tails, and shells were discarded as waste. This shrimp waste could pollute the environment around the factory so it needed to be utilized. So far, shrimp shells had only been used as ingredients for making crackers, shrimp paste, and animal feed supplements. The remaining shrimp shells that had been separated were made into chitosan which was then subjected to characterization tests. The three steps of the chitosan isolation process were deproteinization, demineralization, and deacetylation. The analytical tests carried out were testing the water content, ash content, and functional groups contained in chitosan which were identified using the Fourier Transform Infra Red (FT-IR) Spectrophotometer. Based on the test results, there was a moisture content of 9.27% ??and an ash content of 1.69% in the chitosan samples made from shrimp shells. Functional groups of shrimp shell chitosan were identified using FT-IR characteristics. The -NH- group, which was represented by the N-H and O-H stretching groups, could be seen in the absorption band 1456.26 in the wave range 3000–30500. The conclusion of this study was that chitosan could be extracted from shrimp shells and meet the characterization criteria.